Trends in mobility in India: issues of labour market integration and exclusion of vulnerable sections of the population. Issue 4 (2nd October 2019) - Kundu, Amitabh
ABSTRACT: This paper analyses the proposition that the process of migration and urbanization in India has opened up in recent years, enabling people to move freely and leading to labour market integration, using data from the population census and National Sample Survey (NSS). Based on a critical examination of methodological and data-related issues and the insights on migration gained from the recent Economic Survey and India Human Development Survey, it questions the thesis that mobility in general has gone up significantly notwithstanding the increased mobility and absorption of poor and unskilled women in low-level service sector jobs, particularly in urban areas. Taking the case of the Muslim population, it argues that migration of socioeconomically vulnerable sections of the population has gone down.